A Case–Control Seroprevalence Study on the Association Between Toxoplasma gondii Infection and Bipolar Disorder - Alvarado-Esquivel, Cosme; Estrada-Martínez, Sergio; Pérez-Alamos, Alma Rosa (Frontiers in Psychiatry, 2019)
Background & Aims: Infection with the parasite Toxoplasma gondii (T. gondii) has been associated with bipolar disorder in several countries other than Mexico. Therefore, we sought to determine the association between seropositivity to T. gondii and bipolar disorder in a Mexican population. Methods: We performed an age- and gender-matched case-control study of 66 patients with bipolar disorder (WHO ICD-10 code: F31) and 396 subjects without this disorder from the general population. Anti-Toxoplasma IgG and IgM antibodies were determined using commercially available enzyme-linked immunoassays. Results: Six (9.1%) of the 66 patients with bipolar disorder and 22 (5.6%) of the 396 controls had anti-T. gondii IgG antibodies (OR=1.7; 95% CI: 0.66-4.36; P=0.26). Stratification by gender and age did not show a difference in seroprevalence between cases and controls. The frequency of high (>150 IU/ml) anti-T. gondii IgG levels was similar in cases (n=2) and in controls (n=12) (OR=1.0; 95% CI: 0.21-4.57; P=1.00). Stratification by ICD-10 F31 codes showed that patients with F31.3 code had a higher seroprevalence of T. gondii infection than their age-and gender-matched controls (OR=16.4; 95% CI: 1.25-215.09; P=0.04). None of the 6 anti-T. gondii IgG seropositive patients with bipolar disorder and 4 (18.2%) of the 22 anti-T. gondii IgG seropositive controls had anti-T. gondii IgM antibodies (P=0.54). Conclusions: Our results suggest that T. gondii seropositivity is not associated with bipolar disorder in general. However, a specific type of bipolar disorder (F31.3) might be associated with T. gondii seropositivity. Further research to elucidate the role of T. gondii infection in bipolar disorder is needed.